The Role Of Ginger Software In Supporting Self-Correction In Speaking: A Perspective Of English Department - Qoyyimah, Nadya Dinul; Siregar, Deasy Yunita (JURNAL MANAJEMEN PENDIDIKAN, 2025)
This study aims to examine the role of Ginger Software in supporting the self-correction process of English Department students in speaking skills. The background of this research lies in the limited ability of students to recognize and correct language errors independently during oral communication. This study employed a qualitative method with a case study approach. Fifteen fourth-semester students who had actively used Ginger Software for at least one semester were selected as participants. Data were collected through interviews, direct observation, and documentation using a Google Form designed to capture students’ use of Ginger during speaking practice. The findings revealed that Ginger assisted students in identifying linguistic errors, enhancing metacognitive awareness, and improving confidence and motivation in English speaking. Furthermore, Ginger encouraged collaborative learning. These findings indicate that Ginger Software is an effective technological tool for supporting self-correction and the development of speaking skills among English Department students.